How We Read Tales, Fury, Nothing, Sound - Akbari, Suzanne Conklin; Heller, Kaitlin; Project Muse. (Punctum Books, 2019)
"What do we do when we read? Reading can be an act of consumption or an act of creation. Our "work reading" overlaps with our "pleasure reading," and yet these two modes of reading engage with different parts of the self. It is sometimes passive, sometimes active, and can even be an embodied form. The contributors to this volume share their own histories of reading in order to reveal the shared pleasure that lies in this most solitary of acts - which is also, paradoxically, the act of most complete plenitude. Many of the contributors engage in academic writing, and several publish in other genres, including poetry and fiction; some contributors maintain an active online presence. All are engaged with reading's capacity to stimulate and excite as well as to frustrate and confuse. The synergies and tensions of online reading and print reading animate these thirteen contributions, generating a sense of shared community. Together, the authors open their libraries to us. This is how we read. Table of Contents // Suzanne Conklin Akbari / "Introduction: Practicing Reading, Reading Practice" Irina Dumitrescu / "Reading Lessons" Anna Wilson / "I Like Knowing What is Going to Happen" Suzanne Conklin Akbari / "Read It Out Loud" Jessica Hammer / "From When We Read" Lochin Brouillard / "De Vita Lochini, or Commentary on a Life of Reading" Chris Piuma / "How I Read" Stephanie Bahr / "How I Read, a History; or 'San Francisco Banking Contains No Trans Fats'" Alexandra Atiya / "Text to Speech" Jonathan Hsy / "Phantom Sounds" Kirsty Schut / "On Not Being a Voracious Reader" Kaitlin Heller / "Sleeping Under the Mountain" Jennifer Jordan / "Reading to Forget, Reading to Remember" Brantley Bryant / "Best Practice Tips and Strategies for Academic Reading to Maximize Your Time and Productivity" Kaitlin Heller / "Afterword: The Parlor Scene""--
Description based on print version record.
Keywords: Electronic books